At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Ask your questions and receive detailed answers from professionals with extensive experience in various fields. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
To find the solutions to the equation [tex]\(x^3 + 6x^2 - 40x = 192\)[/tex], we need to understand where the graph of the function [tex]\( y = x^3 + 6x^2 - 40x \)[/tex] intersects the horizontal line [tex]\( y = 192 \)[/tex].
Let's rephrase the problem into one equation by setting the two equations equal to each other:
[tex]\[ x^3 + 6x^2 - 40x = 192 \][/tex]
But for clarity of understanding, we'll convert it to:
[tex]\[ x^3 + 6x^2 - 40x - 192 = 0 \][/tex]
Now, let's solve this polynomial equation step-by-step to find the values of [tex]\( x \)[/tex].
### Step-by-Step Solution
1. Equation Setup:
[tex]\[ x^3 + 6x^2 - 40x - 192 = 0 \][/tex]
2. Finding Rational Roots:
By the Rational Root Theorem, potential rational roots of the polynomial are the factors of the constant term (-192) divided by the factors of the leading coefficient (1). Hence, the possible rational roots are:
[tex]\[ \pm 1, \pm 2, \pm 3, \pm 4, \pm 6, \pm 8, \pm 12, \pm 16, \pm 24, \pm 32, \pm 48, \pm 64, \pm 96, \pm 192 \][/tex]
3. Testing Potential Roots:
Start by checking some of the potential roots using substitution.
- Testing [tex]\( x = -8 \)[/tex]:
[tex]\[ (-8)^3 + 6(-8)^2 - 40(-8) - 192 = -512 + 384 + 320 - 192 \][/tex]
[tex]\[ = 0 \][/tex]
Since this yields 0, [tex]\( x = -8 \)[/tex] is a root.
4. Polynomial Division:
Use polynomial long division or synthetic division to divide the original polynomial by [tex]\( (x + 8) \)[/tex], since [tex]\( x + 8 \)[/tex] is a factor.
Dividing [tex]\( x^3 + 6x^2 - 40x - 192 \)[/tex] by [tex]\( x + 8 \)[/tex] gives:
[tex]\[ x^3 + 6x^2 - 40x - 192 = (x + 8)(x^2 - 2x - 24) \][/tex]
5. Factoring the Quadratic Expression:
We now need to solve the quadratic equation [tex]\( x^2 - 2x - 24 = 0 \)[/tex].
To factor this quadratic, find two numbers that multiply to -24 and add to -2.
[tex]\[ x^2 - 2x - 24 = (x - 6)(x + 4) \][/tex]
6. Finding Additional Roots:
Set the factors equal to zero:
[tex]\[ x - 6 = 0 \quad \Rightarrow \quad x = 6 \][/tex]
[tex]\[ x + 4 = 0 \quad \Rightarrow \quad x = -4 \][/tex]
### Summary and Verification
We have found the roots of the polynomial: [tex]\(x = -8\)[/tex], [tex]\(x = -4\)[/tex], and [tex]\(x = 6\)[/tex]. Verify these solutions by substituting back into the original equation:
[tex]\[ x^3 + 6x^2 - 40x - 192 = 0 \][/tex]
- For [tex]\( x = -8 \)[/tex]:
[tex]\[ (-8)^3 + 6(-8)^2 - 40(-8) - 192 = -512 + 384 + 320 - 192 = 0 \][/tex]
- For [tex]\( x = -4 \)[/tex]:
[tex]\[ (-4)^3 + 6(-4)^2 - 40(-4) - 192 = -64 + 96 + 160 - 192 = 0 \][/tex]
- For [tex]\( x = 6 \)[/tex]:
[tex]\[ 6^3 + 6(6^2) - 40(6) - 192 = 216 + 216 - 240 - 192 = 0 \][/tex]
Thus, the solutions to the equation [tex]\( x^3 + 6x^2 - 40x = 192 \)[/tex] are:
[tex]\[ \boxed{x = -8, x = -4, x = 6} \][/tex]
Let's rephrase the problem into one equation by setting the two equations equal to each other:
[tex]\[ x^3 + 6x^2 - 40x = 192 \][/tex]
But for clarity of understanding, we'll convert it to:
[tex]\[ x^3 + 6x^2 - 40x - 192 = 0 \][/tex]
Now, let's solve this polynomial equation step-by-step to find the values of [tex]\( x \)[/tex].
### Step-by-Step Solution
1. Equation Setup:
[tex]\[ x^3 + 6x^2 - 40x - 192 = 0 \][/tex]
2. Finding Rational Roots:
By the Rational Root Theorem, potential rational roots of the polynomial are the factors of the constant term (-192) divided by the factors of the leading coefficient (1). Hence, the possible rational roots are:
[tex]\[ \pm 1, \pm 2, \pm 3, \pm 4, \pm 6, \pm 8, \pm 12, \pm 16, \pm 24, \pm 32, \pm 48, \pm 64, \pm 96, \pm 192 \][/tex]
3. Testing Potential Roots:
Start by checking some of the potential roots using substitution.
- Testing [tex]\( x = -8 \)[/tex]:
[tex]\[ (-8)^3 + 6(-8)^2 - 40(-8) - 192 = -512 + 384 + 320 - 192 \][/tex]
[tex]\[ = 0 \][/tex]
Since this yields 0, [tex]\( x = -8 \)[/tex] is a root.
4. Polynomial Division:
Use polynomial long division or synthetic division to divide the original polynomial by [tex]\( (x + 8) \)[/tex], since [tex]\( x + 8 \)[/tex] is a factor.
Dividing [tex]\( x^3 + 6x^2 - 40x - 192 \)[/tex] by [tex]\( x + 8 \)[/tex] gives:
[tex]\[ x^3 + 6x^2 - 40x - 192 = (x + 8)(x^2 - 2x - 24) \][/tex]
5. Factoring the Quadratic Expression:
We now need to solve the quadratic equation [tex]\( x^2 - 2x - 24 = 0 \)[/tex].
To factor this quadratic, find two numbers that multiply to -24 and add to -2.
[tex]\[ x^2 - 2x - 24 = (x - 6)(x + 4) \][/tex]
6. Finding Additional Roots:
Set the factors equal to zero:
[tex]\[ x - 6 = 0 \quad \Rightarrow \quad x = 6 \][/tex]
[tex]\[ x + 4 = 0 \quad \Rightarrow \quad x = -4 \][/tex]
### Summary and Verification
We have found the roots of the polynomial: [tex]\(x = -8\)[/tex], [tex]\(x = -4\)[/tex], and [tex]\(x = 6\)[/tex]. Verify these solutions by substituting back into the original equation:
[tex]\[ x^3 + 6x^2 - 40x - 192 = 0 \][/tex]
- For [tex]\( x = -8 \)[/tex]:
[tex]\[ (-8)^3 + 6(-8)^2 - 40(-8) - 192 = -512 + 384 + 320 - 192 = 0 \][/tex]
- For [tex]\( x = -4 \)[/tex]:
[tex]\[ (-4)^3 + 6(-4)^2 - 40(-4) - 192 = -64 + 96 + 160 - 192 = 0 \][/tex]
- For [tex]\( x = 6 \)[/tex]:
[tex]\[ 6^3 + 6(6^2) - 40(6) - 192 = 216 + 216 - 240 - 192 = 0 \][/tex]
Thus, the solutions to the equation [tex]\( x^3 + 6x^2 - 40x = 192 \)[/tex] are:
[tex]\[ \boxed{x = -8, x = -4, x = 6} \][/tex]
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.